Status and trends of human-wildlife conflict: A case study of Lelep and Yamphudin region, Kanchenjunga Conservation Area, Taplejung, Nepal - Sherchan, Roshan; Bhandari, Ananta (Conservation Science, 2017)
Aim Human-wildlife conflict is one of the major challenges in Kanchenjunga Conservation Area. It may erode public support in wildlife conservation. Here, we review the extent to which wildlife damages livestock and crops. Location Lelep and Yamphudin region, Kanchenjunga Conservation Area, Taplejung, Nepal Materials and methodsThe study employed a combination of surveying methods such as focus group discussion, key informant interview and field observation from 21 July to 06 August 2013. Focus group discussion was done primarily with the representatives of snow leopard conservation committee in Lelep and Yamphudin. Key Findings Livestock depredation in Ghunsa valley, Lelep village development committee was increasing with an annual average loss rate of 11% in ten years (2005- 2014). Despite community-based insurance schemes, loss has increased to 28% from 17.2% in 2014. No retaliatory killings of snow leopards were reported since 2005, which may be attributable to the insurance scheme. In Yamphudin, the average annual livestock loss rate was 4.7% from 2005 to 2014, mostly by wild dogs. Similarly, crop damage was a severe problem in Yamphudin, mostly by the Himalayan black bear, palm civet, barking deer, rhesus monkey and porcupine. Conservation implication Although strict guarding was effective to reduce conflict, alternative strategy is needed that requires minimum human involvement. Premium and relief amount is inadequte. It therefore needs a thorough revision. Predator proof corals in Lonak, Dhudhpokhari, Ramjer and Dasa pasture can be effective means to reduce the potential conflict.